ANALISIS PERBANDINGAN EFEKTIVITAS VEGETASI DAN NAUNGAN BUATAN DALAM MENINGKATKAN KENYAMANAN TERMAL RUANG TERBUKA KAMPUS - Syeril salsabella; Eddy Prianto (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: Global warming and massive urbanization have created significant challenges in managing thermal comfort in campus open spaces, particularly in tropical climate regions. This research analyzes the comparative effectiveness of vegetation and artificial shading in improving thermal comfort in campus open spaces, with case studies in three different locations at Diponegoro University: S3 Garden (with artificial shading), S2 Garden (with dense vegetation), and Building A Front Garden (with minimal natural shading). Through a quantitative approach with 24-hour temperature and humidity observations, the research reveals significant differences in thermal performance across the three locations. The S2 Garden with dense vegetation demonstrates the best performance in creating balanced thermal comfort, maintaining an average temperature of 28.5°C with approximately 78% humidity through evapotranspiration processes. Meanwhile, artificial shading in the S3 Garden, although effective in controlling temperature increases up to 34.5°C, shows limitations in regulating humidity, which drops to 41.9% during daytime. The area with minimal shading experiences the most extreme conditions, with temperatures reaching 36.9°C and the largest humidity fluctuations. Research findings indicate that vegetation integration is the most effective strategy in creating sustainable thermal comfort in tropical campus environments, capable of combining temperature control and humidity regulation through natural processes. This research contributes to the development of design guidelines for thermally comfortable and sustainable campus open spaces. Keyword: Vegetation, Artificial Shading, Thermal Comfort, Campus Open Spaces, Abstrak: Pemanasan global dan urbanisasi yang masif telah menciptakan tantangan signifikan dalam pengelolaan kenyamanan termal di ruang terbuka kampus, terutama di kawasan beriklim tropis. Penelitian ini menganalisis perbandingan efektivitas antara vegetasi dan naungan buatan dalam meningkatkan kenyamanan termal di ruang terbuka kampus, dengan studi kasus di tiga lokasi berbeda di Universitas Diponegoro: Taman S3 (dengan naungan buatan), Taman S2 (dengan vegetasi padat), dan Taman Depan Gedung A (dengan naungan alami minim). Melalui pendekatan kuantitatif dengan pengamatan suhu dan kelembaban selama 24 jam, penelitian mengungkapkan perbedaan signifikan dalam kinerja termal di ketiga lokasi tersebut. Taman S2 dengan vegetasi padat menunjukkan kinerja terbaik dalam menciptakan kenyamanan termal yang seimbang, mampu mempertahankan suhu rata-rata 28,5°C dengan kelembaban sekitar 78% melalui proses evapotranspirasi. Sementara itu, naungan buatan di Taman S3, meskipun efektif dalam mengendalikan kenaikan suhu hingga 34,5°C, menunjukkan keterbatasan dalam mengatur kelembaban yang turun hingga 41,9% pada siang hari. Area dengan naungan minim mengalami kondisi paling ekstrem, dengan suhu mencapai 36,9°C dan fluktuasi kelembaban terbesar. Hasil penelitian menunjukkan bahwa integrasi vegetasi merupakan strategi paling efektif dalam menciptakan kenyamanan termal berkelanjutan di lingkungan kampus tropis, mampu mengombinasikan pengendalian suhu dan pengaturan kelembaban melalui proses alami. Penelitian ini berkontribusi pada pengembangan pedoman desain ruang terbuka kampus yang nyaman secara termal dan berkelanjutan. Kata Kunci: Vegetasi, Naungan Buatan, Kenyamanan Termal, Ruang Terbuka Kampus